The Translation of Hospital Management Models in European Health Systems: A Framework for Comparison. (7th August 2013) - Kirkpatrick, Ian; Bullinger, Bernadette; Lega, Federico; Dent, Mike
Abstract : In this paper we develop a framework for comparing changes in the management of public hospitals across different national health systems, drawing on insights from institutional theory. Using a range of secondary sources we show how one particular form of hospital management, pioneered originally at the Johns Hopkins Hospital in Baltimore, has been translated differently in four health systems: England, Denmark, Italy and France. This analysis builds on the notion of editing rules, which derive from the institutional context, and illustrates how these rules broaden our understanding of variable translations of global templates for hospital management. The paper concludes by highlighting wider implications for theory and policy.